Fontanel Size from Birth to 24 Months of Age in Iranian Children - ESMAEILI, Mohammad; ESMAEILI, Marjan; GHANE SHARBAF, Fatemeh; BOKHARAIE, Shirin (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: Esmaeili Mo, Esmaeili Ma, Ghane Sharbaf F, Bokharaie Sh. Fontanel Size from Birth to 24 Months of Age in Iranian Children. Iran J Child Neurol. Autumn 2015;9(4):15-23. Abstract Objective Diagnosis of abnormal fontanel size, a potential clue to recognition of different disorders, requires an understanding of the wide variation of normal fontanel size. The anterior fontanel is the largest, prominent and most important for clinical evaluation. The aim of this study was to establish and define normal range of fontanel size from birth to 24 months of age in healthy Iranian children that might be generalized to other populations. Materials & Methods Totally, 550 subjects enrolled randomly in this cross sectional study. They were apparently normal healthy children, from birth to 24 months of age, including 208-term newborn and 342 infant from birth to 2 yr old. Fontanel size was measured and recorded as the mean of the length (anterior- posterior dimension) and width (transverse dimension). Mean anterior fontanel sizes in our samples were classified for periods of 3 months. Nomograms and statistical analyses were performed and depicted by Excel Microsoft Office 2007 and two-tailed t-test respectively. Results The mean ±2SD of anterior fontanel size was 2.55±1.92 cm in newborns, 3.37±2.48 (largest size) in 3 months of age. It was closed in all cases in 15-18 months of age. The mean posterior fontanel size was 0.8 cm in newborns and closed in all infants in 2 months of age. There was no significant difference in anterior fontanel size between two genders except in newborn and 6-9 months old (P>0.05). Conclusion Abnormal fontanel can indicate a serious medical condition. Therefore, it is important to understand normal variations, to utilize standardized techniques for measurement and appropriate standards of normal range in different age groups and populations. This study provides a normal range of mean fontanel size in Iranian infants as a local reference. It might be generalized to other populations.